(untitled) (Texas Journal of Engineering and Technology, 2023)
nowadays, along with the increase in the volume of data, ensuring its protection is one of the important issues. The best way to ensure data confidentiality is the cryptographic method. One of the main parameters of public-key cryptoalgorithms is a prime number. This paper presents an analysis of probabilistic algorithms to check the primality number and improves the Rabin Milner algorithm to reduce the number of false witnesses